Breeding of the Dormant Thermosensitive Genic Male-Sterile Lines of Early Rice to Overcome Pre-Harvest Sprouting of the Hybrid Seeds - Xiaoyu Chen (Agronomy, 2018)
The pollen development of male-sterile lines should be conducted during the high temperature season to ensure the sterility of male-sterile line pollen and the safety of hybrid seed production in the breeding of thermosensitive genic male-sterile (TGMS) lines of early rice. However, the mature hybrid rice seeds are prone to pre-harvest sprouting (PHS) during hot, rainy days, which leads to the decrease of hybrid rice seed quality or a loss of utilization value. In this study, with an aim to bring a dormancy trait from the dormant genotype to the current low-dormant TGMS lines, a common wild rice “Chaling” (Oryza rufipogon), which has strong seed dormancy, a large black stigma, and a high exsertion rate, was hybridized with the early rice TGMS line “Zhu 1S,” which often exhibits PHS. After screening for early maturing and seed dormancy, the early rice “Yezao S” and “Yezhuzao S,” with the characteristic of seed dormancy, were selected. The critical temperature of high temperature sterility for these two male-sterile lines was below 23.5 °C. The stigma of “Yezao S” was black and its exsertion rate was 79.9%, while “Yezhuzao S” had a colorless stigma with an exsertion rate of 76.8%. The expression of the genes OsNCEDs in “Yezao S” and “Yezhuzao S” were significantly higher than that in “Zhu 1S” the 15th day after heading, and the abscisic acid (ABA) content was also higher than that of “Zhu 1S” the 20th day after heading. The results indicated that introducing the dormancy characteristics from wild rice “Chaling” into the early rice TGMS lines was an effective way to prevent PHS.